The Influence of MBKM Project-Based Learning on Problem Solving of Educational Technology Undergraduate Students at Bina Mandiri University Gorontalo - Frezy Paputungan (International Journal of Computer Technology and Science, 2025)
This research aims to determine the impact of Project Based Learning (MBKM) on Problem Solving for Undergraduate Students in Educational Technology at Bina Mandiri University, Gorontalo. The research method used is a qualitative and quantitative approach at four research stages. According to Creswel and Clark, mixed methods research is a research design with philosophical assumptions as well as being an inquiry method. As a methodology, this mixed research involves philosophical assumptions that guide the direction of data collection and analysis, as well as cultivating qualitative and quantitative research approaches throughout many phases of the research process. This research is in the first stage, namely identifying problem solving for Bachelor of Educational Technology students and measuring the effectiveness of MBKM project-based learning at UBMG. The results of the research show that project-based learning (MBKM) can influence Problem Solving for students in the Bachelor of Educational Technology study program at Bina Mandiri University, Gorontalo. This can be seen from the achievement of the problem solving method indicator for the Educational Technology S1 PRODI students, which was initially 75%, increasing to 87% after participating in project-based learning (MBKM) for one semester. The conclusion of this research is that project-based learning (MBKM) has a positive impact on improving problem solving skills in undergraduate students in educational technology so that it can be applied to subsequent learning processes.